2016
DOI: 10.1039/c5ta10031c
|View full text |Cite
|
Sign up to set email alerts
|

Beyond graphene foam, a new form of three-dimensional graphene for supercapacitor electrodes

Abstract: Graphene foam (GF) is a three-dimensional (3D) graphene structure that has been intensively studied as an electrode material for energy storage applications. Here we report a new design and fabrication process of an electrode material called graphene pellet (GP) for energy storage applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…The fabricated device is very flexible and the GP itself showed excellent electromechanical properties. As reported earlier, after 5000 bending cycles the resistance increased not more than 7.3% . The scanning electron microscopy (SEM) image in Figure a illustrates that the GP interdigitated pattern is composed a porous 3D graphene structure with interconnected flakes.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…The fabricated device is very flexible and the GP itself showed excellent electromechanical properties. As reported earlier, after 5000 bending cycles the resistance increased not more than 7.3% . The scanning electron microscopy (SEM) image in Figure a illustrates that the GP interdigitated pattern is composed a porous 3D graphene structure with interconnected flakes.…”
supporting
confidence: 69%
“…The electrical conductivity of our 3D graphene is higher than the conventional 3D graphene foam and 3D rGO . Our previous study showed that the 3D GP has a potential to significantly increase its electrical conductivity upon compression …”
mentioning
confidence: 82%
See 2 more Smart Citations
“…On the other hand, as different nanoparticles been invented and characterized, many of them are explored in various applications including electrochemistry . Since they were first discovered, carbon nanotubes (CNTs) have been attracting increased attention thanks to their excellent electrochemical properties, including wide potential window, fast electron transfer rate and large surface area . Applications with CNTs have a wide range of use, including in biomedicine, nanoelectronics, environmental engineering and electrochemical sensing .…”
Section: Carbon Nanotubes and The Electroactivity Of Carbon Nanotubesmentioning
confidence: 99%